a the Systematic Literature Review Pengaruh Penggunaan Media Question Card Terhadap Hasil Belajar Murid - Hemi Shasfiyah; Rahmawati Darussyamsu (LP2M UIN Ambon, 2025)
Student learning outcomes are an indicator of educational success that is influenced by internal and external factors. A major problem that often arises in the classroom is a lack of variety in teaching methods, which leads to boredom and passivity among students. Question cards are an innovative learning medium that is simple yet interactive and can increase student participation. This study aims to generalize and identify the success of applying question cards in improving student learning outcomes. This study applies a qualitative approach with a Systematic Literature Review (SLR) design. Based on a literature review, the use of question cards as a medium in learning activities has been proven to have a significant positive effect on increasing student engagement and learning outcomes beyond the learning outcomes achieved through conventional methods. This finding provides a theoretical basis for educators to maximize the use of innovative instructional media in the digital age.